New wavelength-dependent femtosecond pulsed LASER cleaning: A case study with stones of different provenance locality, Portugal - Rahman, Md Ashiqur (2022)
Laser cleaning techniques have been considered amongst the most impactful contributions of Physics towards the restoration of stonework. Contamination and deterioration products in stones eliminated by laser-assisted techniques is a new and promising development that may highlight the use of laser cleaning methodology in this sector. This research work reports on studies aimed to evaluate the use of ultrafast femtosecond (fs) pulsed lasers for the removal of contaminants on significant stone surfaces with different locality from Portugal. A series of studies have been carried out to assess the controlled laser cleaning parameters using two different laser systems: a 238 fs pulsed UV laser with emission at 343 nm and a 228 fs pulsed n-IR laser with emission at 1030 nm. In both cases, line scan pulse mode was employed to explore contaminant removal efficiency while, at the time, assessing the degree of damage produced to the underlying original substrate surface. Adequate repetition-rate generation, wavelength-dependent absorption and materials thermal properties are amongst the parameters considered, and the main results obtained will be presented and discussed in an effort to evaluate the potential that these new types of lasers offer towards an increased cleaning efficiency of stones with deteriorated surfaces.